1985
DOI: 10.1111/j.1469-8137.1985.tb02802.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF GROWTH REGULATORS ON THE IN VITRO GERMINATION AND TUBE GROWTH OF MAIZE (ZEA MA YS L.) POLLEN FROM PLANTS RAISED UNDER SODIUM CHLORIDE SALINITY

Abstract: SUMMARYPollen grains, collected from maize plants raised under conditions of 0, 80, 120 and 160 meq 1"ŝ alinity, were used to investigate the effect of various growth regulators on in I'itro germination and tube growth. Indole-3-acetic acid had no effect on germination, irrespective of the source of pollen, whether derived from plants grown under saline or non saline conditions. However, its lower concentrations enhanced tube growth in pollen from salinized plants. Gibberellic acid at a concentration of 1 mg 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It has been reported previously that salt stress reduces the supply of cytokinin from root to shoot (Naqvi and Ansari 1974), and also the recovery of diffusible auxin from maize coleoptile tips (Itai et al 1968). Indeed, the exogenous application of plant growth regulators (PGRs), e.g., gibberellins (Prakash and Parthapasenan 1990;Afzal et al 2005), auxins (Gul et al 2000;Khan et al 2001Khan et al , 2004, cytokinins (Dhingra and Varghese 1985;Khan and Weber 1986;Gul et al 2000) produced some benefit in alleviating the adverse effects of salt stress and they also improve germination, growth, fruit setting, fresh vegetable and seed yields and yield quality (Saimbhi 1993). It is also suggested that root colonizing bacteria which produce phytohormones, when bound to the seed coat of a developing seedling, may act as a mechanism for plant growth stimulation and these organisms can prevent the deleterious effects of stresses from the environment (Lindberg et al 1985;Frankenberger and Arshad 1995).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported previously that salt stress reduces the supply of cytokinin from root to shoot (Naqvi and Ansari 1974), and also the recovery of diffusible auxin from maize coleoptile tips (Itai et al 1968). Indeed, the exogenous application of plant growth regulators (PGRs), e.g., gibberellins (Prakash and Parthapasenan 1990;Afzal et al 2005), auxins (Gul et al 2000;Khan et al 2001Khan et al , 2004, cytokinins (Dhingra and Varghese 1985;Khan and Weber 1986;Gul et al 2000) produced some benefit in alleviating the adverse effects of salt stress and they also improve germination, growth, fruit setting, fresh vegetable and seed yields and yield quality (Saimbhi 1993). It is also suggested that root colonizing bacteria which produce phytohormones, when bound to the seed coat of a developing seedling, may act as a mechanism for plant growth stimulation and these organisms can prevent the deleterious effects of stresses from the environment (Lindberg et al 1985;Frankenberger and Arshad 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Le Van et al (2004) showed that an acid (pI 3.8) and low molecular weight (23 kD) protein was identified in Altreated Cayenne root tips following Al stress, but not in no Al-treated one. About the study of salt-tolerant plants, many researchers recognized that salt-tolerant proteins in roots which enhance salt-tolerance of the plants (Singh and Haseguwa, 1987;Degeuhandt et al, 2000;Dhingra and Varghese, 1985). The salt-tolerant proteins and physiological effect of tomato roots in high salt environment have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In water-defi cit environment, the closing of stomata reduces the CO 2 fi xation that disturbs the photosynthetic activity of the plants (Chatrath et al 2000 ); however, reverse has been observed by application of IAA under such condition . Dhingra and Varghese ( 1985 ) GA3 and IAA Seed priming with phytohormones enhanced germination and radicle and plumule length. 8 h was more effective than 16 h in all aspects Saeedipour ( 2013 ) GA3 and IAA EDTA signifi cantly reduced the plant growth and dry biomass, while application of phytohormones improved it.…”
Section: Phytohormones and Plant Stress Tolerancementioning
confidence: 96%